Media and health promotion in times of COVID-19 - Silva, Eduardo de Sousa Martins e (2020)
The access to information is one of the most important ways of promoting health. Understanding the current circumstances helps the population to take a stand and face the COVID-19 pandemic. However, the overload of news and data, often false, poses risks to mental health and well-being. It is observed, fomented by biased news, which stimulates panic, an increase in, global levels of anxiety, depression, among others psychological disorders. It is necessary to inform individuals about the pandemic without splurge. Therefore, this article aims to analyse how the media and social networks are related with health promotion during the pandemics of COVID-19 and its difficulties produced by “infodemic”. An integrative bibliographic review was carried out using scientific articles from the last ten years, from PUBMED database, with the descriptors: Communication; Promotion; Pandemic; COVID-19; Health. In addition with the books “Comunicação e saúde” and “Health promotion practice”.